Analysis of total quality management in the secondary manufacturing department of British American Tobacco Bangladesh - Siddiqua, Ayesha (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.